Restorative justice: a qualitative analysis of school security perspectives - Robinson, Luz E. (Contemporary justice review, 2021)
Grounded in Restorative Justice theory, the current study examines the perspectives of School Resource Officers (SROs) and other School Security Personnel (SSPs) during a professional development training on restorative-problem solving. Specifically, focusing on how school security staff are currently using restorative justice in their work, how they can use these practices in the future, and any variations in perspectives towards restorative justice based on their job title. A qualitative phenomenological methodology was used to analyze qualitative responses to training logs from SROs and SSPs (n = 99). Throughout the module, participants were asked to reflect on five different situations and provide examples of how they would address these issues using restorative justice. Codes and memos were used to summarize the themes across participants. Both SROs and SSPs are aware of restorative practices and use them to some capacity in their roles. However, additional training is needed to ensure that practices are used consistently and effectively across positions and schools. To abolish the U.S. school-to-prison pipeline, all school staff including security should receive mandatory, ongoing, evidence-based professional development for school-wide implementation of restorative justice as an alternative to punitive disciplinary strategies that disproportionately harm students of color and their families.